Preventing bacterial disease in poultry in the post-antibiotic era: a case for innate immunity modulation as an alternative to antibiotic use - Adams, James R. G.; Mehat, Jai; La Ragione, Roberto; Behboudi, Shahriar (Frontiers in Immunology, 2023)
The widespread use of antibiotics in the poultry industry has led to the emergence of antibiotic-resistant bacteria, which pose a significant health risk to humans and animals. These public health concerns, which have led to legislation limiting antibiotic use in animals, drive the need to find alternative strategies for controlling and treating bacterial infections. Modulation of the avian innate immune system using immunostimulatory compounds provides a promising solution to enhance poultry immune responses to a broad range of bacterial infections without the risk of generating antibiotic resistance. An array of immunomodulatory compounds have been investigated for their impact on poultry performance and immune responses. However, further research is required to identify compounds capable of controlling bacterial infections without detrimentally affecting bird performance. It is also crucial to determine the safety and effectiveness of these compounds in conjunction with poultry vaccines. This review provides an overview of the various immune modulators known to enhance innate immunity against avian bacterial pathogens in chickens, and describes the mechanisms involved.